Gonad atrophy caused by disseminated neoplasia in Mytilus chilensis cultured in the beagle channel, Tierra del Fuego province, Argentina - Cremonte, Florencia (2011)
Disseminated neoplasia in cultured Mytilus chilensis (Mytilidae) from the Beagle Channel (Tierra del Fuego Province) in southern Argentina has been detected for the first time. The disease is characterized by the infiltration of neoplastic cells with enlarged nuclei and high nuclear-to-cytoplasmic volume ratios. All specimens with disseminated neoplasia were female and exhibited gonadal atrophy in advanced stages of the disease. The high prevalence reported (13.3%) indicates an epizootic level.